2019
DOI: 10.1155/2019/1862531
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Intestinal Antiviral Innate Immunity and Immune Evasion Strategies of Porcine Epidemic Diarrhea Virus

Abstract: Porcine epidemic diarrhea virus (PEDV) infection causes watery diarrhea, dehydration, and high mortality in neonatal pigs, due to its clinical pathogenesis of the intestinal mucosal barrier dysfunction. e host's innate immune system is the first line of defence upon virus invasion of the small intestinal epithelial cells. In turn, the virus has evolved to modulate the host's innate immunity during infection, resulting in pathogen virulence, survival, and the establishment of successful infection. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Induction of IAP in the small intestine was present in obese mice supplemented with a high-fat, apple pectin diet [20]. Moreover, Ifn α, Isg 15, and Mx1 genes, which are activated upon microbial infections such as viral invasions, play a critical role in innate immunity [38]. In our study, these genes were notably upregulated and revealed that modified SmP and SmPNPs can exert a protective function in mice duodenum through their immunostimulatory property.…”
Section: Discussionmentioning
confidence: 49%
“…Induction of IAP in the small intestine was present in obese mice supplemented with a high-fat, apple pectin diet [20]. Moreover, Ifn α, Isg 15, and Mx1 genes, which are activated upon microbial infections such as viral invasions, play a critical role in innate immunity [38]. In our study, these genes were notably upregulated and revealed that modified SmP and SmPNPs can exert a protective function in mice duodenum through their immunostimulatory property.…”
Section: Discussionmentioning
confidence: 49%
“…PEDV is suppressed by treating with glutathione-capped Ag 2 S nanoclusters. The principle behind this process is inhibition of RNA synthesis [ 53 ]. There are many viruses that are similar to SARS-CoV-2, so these viruses are used as models for research.…”
Section: Nanomaterials For Treatment Of Covid-19mentioning
confidence: 99%
“…Moreover, glutathione is a well-described and established antioxidant, it participates in detoxification of xenobiotics, regulation of cellular growth, modulation of immune response, and even inherent antibacterial properties ( 21 ), which is an important modulator of antibiotic activity in bacteria ( 22 ). This makes NAC a promising supplement for the piglets to regulate the porcine gut microbiome and alleviate dysbiosis during pathogenic infection ( 23 ), including PEDV ( 24 ). Our previous study also demonstrated that dietary NAC supplementation improved intestinal integrity and functions in PEDV-infected piglets ( 25 ).…”
Section: Introductionmentioning
confidence: 99%